Aortic thromboendarterectomy and patch aortoplasty as the treatment of choice for severe blunt abdominal aortic injury in children with aortic occlusion - Simar Goyal, BA; Ethan Vieira, MS; Charles A. West, Jr., MD; John L. Crawford, MD; Marty Knott, DO, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
Blunt abdominal aortic injury is described infrequently in children. We report the successful surgical treatment of a 13-year-old boy who initially presented with an infrarenal abdominal aortic dissection that progressed to acute aortic occlusion after sustaining a blunt seat belt injury from a motor vehicle accident when restrained as a backseat passenger. Our case demonstrates the utility and durability of longitudinal aortotomy and thromboendarectomy with patch aortoplasty for the treatment of pediatric patients with blunt abdominal aortic injury resulting in aortic occlusion. This procedure can be performed expeditiously and may prove to be the technique of choice in patients who sustain such injuries.